Rwanda-Smart Nkunganire System (SNS) Fertilizer Recommendation Tool—Innovation Packaging and Scaling Readiness (IPSR) Analysis for Smart Agronomy - Mudereri, B.T.; Kihoro, E.; Kangethe, E.; Rabourn, T.R.; Ogunsamni, T.; Uzamushaka, S.; Mwizerwa, H.; Kihiu, E.; Nshimiyimana, J.C.; Kayumba, J.; Nsabimana, E.; Sartas, M.; et al. (2024)
Executive summary The SNS Fertilizer Recommendation Innovation Packaging and Scaling Readiness (IPSR) Workshop was held on 30 April 2024 in Kigali, Rwanda. The workshop aimed to identify challenges, bottlenecks and enabling elements for the Smart Nkunganire System (SNS) fertilizer recommendation tool (SNS-FRT), which provides tailored recommendations for six high-priority crops, benefiting over 1.5 million smallholder farmers in Rwanda. The event, facilitated by CGIAR and funded by Ukama Ustawi in collaboration with the Rwanda Agriculture and Animal Resources Development Board (RAB) and the CGIAR Excellence in Agronomy (EiA) initiative, brought together research, private and public institutions to discuss the system's readiness for scaling. Scaling ambition The scaling team will work together with RAB, BKTechouse, One Acre Fund (OAF), and farmer cooperatives such as the Imbaraga to accomplish the use of the fertilizer recommendation tool for an initial two of the six priority crops through the Smart Nkunganire System (SNS), supported by at least 10 sector agronomists, 200 farmer facilitators, and a total of 10,000 farmers in Rwanda contributing to the achievement the end-of-initiative outcomes for the Ukama Ustawi and EiA initiatives. Furthermore, 10,000 farmers will be selected for the pilot phase of the scaling using standardized scientific methods. The pilot phase will prepare the roll-out to over 1.5 million SNS-registered farmers. Thus, assuming a 20% adoption rate, at least 300,000 farmers will benefit from the fertilizer recommendation tool by 2025. The IPSR workshop The workshop included presentations, discussions, and collaborative ideation sessions focused on analyzing challenges and barriers to scaling SNS-FRT, Identifying and evaluating specific interventions to address these challenges and prioritizing the next steps for enhancing the SNS tool's effectiveness and user experience. Participants delved into topics related to innovation packaging, identifying enablers and solutions, and assessing innovation readiness and use. Through group work and collective discussions, the workshop participants developed a comprehensive understanding of the system's status and future needs. Major challenges, barriers and bottlenecks a. Limited user awareness of the system and limitations in technical navigation within the system. b. Complexity in the SNS system is exacerbated by the number of steps (240 USSD steps to request fertilizer). c. Accessibility of the system due to mobile network limitations causing timeouts. d. The uncertainty in the long-term financial sustainability of the SNS system if the government pulls their support. e. Delays in fertilizer supply to farmers from the time of ordering to the delivery within the entire fertilizer supply chain. Key enablers/ packages The workshop yielded several key insights and actionable recommendations: a. Continuously update and validate the core innovation. b. Awareness creation program to increase knowledge on SNS-FRT. c. SNS-FRT improvement and implementation initiative. d. SNS-FRT user feedback mechanism. e. SNS-FRT compliance program for App users. f. Inclusive business model for enhanced agricultural access. g. Risk aggregator initiative for sustainable fertilizer financing.